Keanekaragaman Tumbuhan Fitoremediasi Di Ekosistem Riparian DAS Citarum - Raizal Fahmi Solihat; Fahriza Luth (Paspalum: Jurnal Ilmiah Pertanian, 2021)
Riparian ecosystems have a protective function of watersheds from pollution. One important component in riparian ecosystem is the presence of phytoremediation plants, which can degrade contamination content. This research is intended to identify the presence of undergrowth that functions as phytoremediation in Bojongsoang District which is one of the areas around the heavily polluted Citarum watershed zone[1]. The method used in this research is vegetation analysis using the quadrant method with 1x1 m2 plot size. Determination of sampling points used purposive sampling method. The results of the study found that the undergrowth as a potential phytoremediation included rumput teki (Cyperus rotundus), Beluntas (Pluchea indica), Alang-alang (Imperata cylindrica), Jejarongan (Chloris barbata), rumput gajah (Cyperus rotundus), and bayam duri (Amaranthus spinosus). Rumput teki (Cyperus rotundus) is phyto-extractions in mercury-contaminated soils and accumulators of Sn, Zn, As, Cu, and Pb. Alang-alang (Imperata cylindrical) is a cyanide phytoremediator which is able to extract Zn from contaminated soil, and absorb Pb from contaminated soil. Beluntas is able to accumulate Cu, Fe, Al, Pb and Zn in their roots, leaves and stems, and the leaves that can absorb Cr. Rumput gajah (Cyperus rotundus) are a Cd accumulator. Bayam duri (Amaranthus spinosus) hyperaccumulator against mercury. Studies on the presence of phytoremediation plants can provide preliminary information on the condition of riparian ecosystems in the Citarum watershed.